Trends of Primary School Teachers Computational Thinking Research: Bibliometric Analysis - Maharani, Swasti; Yuniahastuti, Irna Tri; Prastyaningrum, Ihtiari; Susanti, Vera Dewi; Romandoni, Hendrisa Rizqie; Atmojo, Alief Arida Dhimas (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The growing emphasis on Computational Thinking (CT) skills among elementary school teachers highlights its importance in improving learning quality in the digital era. Despite the extensive focus on CT applications for students, research on the role of teachers in developing CT skills remains limited. This study aims to analyze publication trends, researcher collaboration, and dominant keywords in CT-related research focusing on elementary school teachers from 2015 to 2024. A bibliometric analysis method was employed using data retrieved from Dimensions.ai, which was further analyzed with VOSviewer software. The analysis included mapping author collaboration networks, keyword co-occurrence, and inter-country relationships using bibliographic coupling techniques. The findings show a significant increase in CT-related publications among elementary school teachers, especially after 2018, with a peak in 2023. Key contributors such as Nasri, Hermita Neni, and Fendrik Muhammad emerged as central figures in advancing CT teaching resources. Keyword analysis revealed that discussions around teacher roles, CT skills, and challenges in implementation dominate the literature. Globally, the United States, Germany, and China are leading in CT research, while Indonesia has made substantial strides in international collaboration. These findings indicate an expanding interest in CT research among elementary school educators and highlight the critical need for more studies focusing on enhancing teachers' CT skills through professional training and resource development. This study provides valuable insights into the evolving landscape of CT-related research and its implications for improving teacher competencies in digital learning environments.